OP54 Short-Term Impact of the Smokefree Legislation in England on Hospital Admissions for Asthma Among Adults. (17th September 2012) - Sims, M; Gilmore, A
Abstract : Background: Comprehensive smokefree laws prohibiting smoking in enclosed public places and workplaces have now been introduced in several jurisdictions and there is a growing body of evidence documenting the immediate health benefits to adults, focusing primarily on hospital admissions for heart attacks. A few studies have examined the association between smokefree laws and asthma in adults, but these have limitations such as lacking appropriate adjustment for long-term trends, or having limited statistical power due to a small study population. In this study we investigated the short-term impact of the introduction of smokefree legislation in England on 1st July 2007 on hospital admissions for asthma in adults. Methods: The immediate effect of the legislation was investigated using monthly numbers of emergency admissions for asthma (primary diagnosis, ICD–10 code J45 and J46) in the nine Government Office Regions from April 1997 to December 2010, in the population aged 16 and over. The analysis was conducted using a quasi-Poisson generalised additive model that adjusted for seasonality and region-specific, non-linear, long-term trends. Results: After adjusting for the long-term trend in admissions, we observed a 4.9% (95% CI: 0.6, 9.0) reduction in admissions for asthma immediately after introduction of smokefree legislation in the population as a whole. This implies that almost 1900 emergency admissions for asthma were prevented during the first year of the legislation. The reduction in admissions did not vary significantly across regions. Conclusion: Our finding, based on the largest study to date, adds to the expanding body of evidence that smokefree legislation is associated with positive health outcomes. Further research evaluating the impact of legislation on asthma admissions in other jurisdictions is needed in order to support these findings.